Rubber composition and vulcanized rubber

The integration of cellulose nanofibers into chloroprene rubber compositions addresses the issues of high die swell ratios and short scorch times, resulting in improved extrusion properties and mechanical performance.

JP2025056715APending Publication Date: 2025-04-08TOSOH CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024117931
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-26
Filing Date
2024-07-23
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing rubber compositions for extrusion molding, particularly those containing chloroprene rubber, face challenges with high die swell ratios, short scorch times, and compromised mechanical properties such as tensile strength and water resistance.

Method used

A rubber composition comprising chloroprene rubber and cellulose nanofibers, where the cellulose nanofibers have an average fiber diameter of 10 to 300 nm and an average fiber length of 0.3 to 200 μm, is used to achieve improved die swell ratios and scorchability.

Benefits of technology

The rubber composition exhibits a die swell ratio of 1.4 or less at various shear rates and demonstrates excellent scorchability with extended scorch times, while maintaining superior mechanical properties compared to compositions without cellulose nanofibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025056715000001
    Figure 2025056715000001
Patent Text Reader

Abstract

To provide a chloroprene rubber composition having excellent die swell ratio, and, excellent scorch resistance, and a vulcanized rubber.SOLUTION: Using a chloroprene rubber composition that contains the components (A) to (C) below, with a specific die swell ratio, and where t5 is 12 minutes or more and t35 is 18 minutes or more in the Mooney scorch test. (A) Component: Chloroprene rubber that is mercaptan-modified, xanthogen-modified, or sulfur-modified. (B) Component: Cellulose nanofibers that have an average fiber diameter of 10 to 300 nm, an average fiber length of 0.3 to 200 μm, a lignin content of 20 weight % or less, and that hydroxymethyl groups have not been modified with carboxylic acids or carboxyl salts. (C) Component: At least one selected from the group consisting of carbon black, silica, clay, calcium carbonate, talc, titanium dioxide, barium sulfate, aluminum hydroxide, wollastonite, and diatomaceous earth.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a rubber composition and a vulcanized rubber containing chloroprene rubber. [Background technology]

[0002] Among various synthetic rubbers, chloroprene rubber has a good balance of physical properties and is therefore used in a wide range of applications, such as belts, boots, air springs, drawing cloth, vibration-proof rubber, hoses, electric wires, rolls, wipers, gaskets, gloves, and adhesives.

[0003] Among these, hoses, electric wires, rolls, wipers, gaskets, and other products are made by extrusion molding, and the shrinkage rate of the unvulcanized material after extrusion molding (hereinafter referred to as the die swell ratio) affects the dimensions and dimensional accuracy of the subsequent products, as well as the design of the extrusion nozzle. Therefore, for extrusion molding applications, rubber materials with as small a die swell ratio as possible are required.

[0004] For this reason, grades of chloroprene rubber that have a small die swelling ratio for extrusion molding applications are available, but extrusion grade chloroprene rubber tends to have a shorter scorch time than mercaptan-modified chloroprene rubber and sulfur-modified chloroprene rubber.

[0005] Additionally, there are common compounding methods for improving die swell, such as using low-viscosity polymers or adding softeners or plasticizers to lower the rubber viscosity, but there are cases in which shape retention after extrusion molding becomes an issue.

[0006] Furthermore, a method has been devised in which cellulose fiber is added as a compounding agent to reduce die swell, but this method has many problems, such as poor dispersion of the cellulose fiber, deterioration of the finished surface, reduction in tensile strength and elongation after vulcanization, deterioration of water resistance, and deterioration of compression set.

[0007] As another method for suppressing the die swell ratio, a method of mixing an ethylene-vinyl acetate copolymer having a hydroxyl group has been proposed (see, for example, Patent Document 1). In Patent Document 1, the examples and comparative examples are compared in which the hardness after vulcanization is significantly different, but when an ethylene-vinyl acetate copolymer is actually blended and the types and amounts of vulcanization chemicals added are adjusted to achieve the same hardness after vulcanization, and various physical properties are compared, the die swell ratio is improved, but the tensile strength and elongation are significantly reduced.

[0008] Next, as another method for suppressing the die swell ratio, a method of adding a fiber-reinforced thermoplastic composition has been proposed (see, for example, Patent Document 2). However, although the green modulus is significantly improved, the die swell ratio is not so significantly improved. In addition, the mixing temperature for mixing the thermoplastic composition with the rubber is high, making it unsuitable for application to chloroprene rubber. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Japanese Patent Application Publication No. 50-159536 [Patent Document 2] Japanese Patent Application Publication No. 7-330961 Summary of the Invention [Problem to be solved by the invention]

[0010] The present invention has been made in consideration of these problems, and an object of the present invention is to provide a chloroprene rubber composition and a vulcanized rubber which have excellent extrusion characteristics, die swelling ratio, and excellent scorch resistance. [Means for solving the problem]

[0011] Under such a background, the present inventors have conducted intensive research to solve the above problems, and have found that a rubber composition containing chloroprene rubber and cellulose nanofibers has an excellent die swell ratio and excellent scorch resistance. That is, the respective aspects of the present invention are [1] to [4] shown below. [1] Contains the following components (A) to (C): Die swell ratio at a temperature of 70°C and a shear rate of 100 (1 / sec) is 1.4 or less. Die swell ratio at a temperature of 70°C and a shear rate of 300 (1 / sec) is 1.5 or less. Die swell ratio at a temperature of 70°C and a shear rate of 500 (1 / sec) is 1.55 or less. Die swell ratio at a temperature of 70°C and a shear rate of 1000 (1 / sec) is 1.75 or less The chloroprene rubber composition has a t5 of 12 minutes or more and a t35 of 18 minutes or more in a Mooney scorch test. Component (A): mercaptan-modified, xanthogen-modified or sulfur-modified chloroprene rubber. Component (B): 0.1 to 3.5 parts by weight of cellulose nanofibers having an average fiber diameter of 10 to 300 nm, an average fiber length of 0.3 to 200 μm, a lignin content of 20% by weight or less, and hydroxymethyl groups not modified with carboxylic acid or carboxylate salt, per 100 parts by weight of chloroprene rubber. Component (C): 10 to 200 parts by weight in total of at least one selected from the group consisting of carbon black, silica, clay, calcium carbonate, talc, titanium oxide, barium sulfate, aluminum hydroxide, wollastonite, and diatomaceous earth, per 100 parts by weight of chloroprene rubber. [2] The rubber composition according to the above [1], wherein the cellulose nanofibers are unmodified and defibrated only by mechanical treatment. [3] The rubber composition according to the above [1] or [2], wherein the chloroprene rubber contains 3 to 7% by weight of a carboxylic acid or an alkali metal salt of a carboxylic acid. [4] A vulcanized rubber which is a vulcanizate of the rubber composition according to any one of [1] to [3]. Effect of the Invention

[0012] According to the present invention, it is possible to obtain a chloroprene rubber composition and a vulcanized rubber having an excellent die swelling ratio and excellent scorch resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The present invention will be described in detail below.

[0014] The rubber composition according to one embodiment of the present invention contains, per 100 parts by weight of mercaptan-modified, xanthogen-modified or sulfur-modified chloroprene rubber, 0.1 to 3.5 parts by weight of cellulose nanofibers having an average fiber diameter of 10 to 300 nm, an average fiber length of 0.3 to 200 μm, a lignin content of 20% by weight or less, and a hydroxymethyl group not modified with a carboxylic acid or a carboxylate, and further contains 10 to 200 parts by weight of at least one selected from the group consisting of carbon black, silica, clay, calcium carbonate, talc, titanium oxide, barium sulfate, aluminum hydroxide, wollastonite and diatomaceous earth.

[0015] The rubber composition also has a die swell ratio of 1.4 or less at a temperature of 70°C and a shear rate of 100 (1 / sec), a die swell ratio of 1.5 or less at a temperature of 70°C and a shear rate of 300 (1 / sec), a die swell ratio of 1.55 or less at a temperature of 70°C and a shear rate of 500 (1 / sec), and a die swell ratio of 1.75 or less at a temperature of 70°C and a shear rate of 1000 (1 / sec).

[0016] Chloroprene rubber can be obtained by emulsion polymerization of chloroprene or chloroprene and a monomer copolymerizable therewith.

[0017] Examples of monomers copolymerizable with chloroprene include, in addition to sulfur, 2,3-dichloro-1,3-butadiene, 2-cyano-1,3-butadiene, 1-chloro-1,3-butadiene, 1,3-butadiene, styrene, acrylonitrile, methyl methacrylate, methacrylic acid, acrylic acid, and the like. Among these, one or more types can be used in combination and are used appropriately depending on the required physical properties.

[0018] The amount of copolymerizable monomer is not particularly limited, but generally 30 parts by weight or less is used per 100 parts by weight of chloroprene rubber so as not to impair the properties of the chloroprene polymer. In particular, for sulfur, in order to achieve a good balance between heat resistance and physical properties, 3 parts by weight or less, more preferably 1 part by weight or less is used per 100 parts by weight of chloroprene monomer.

[0019] The chloroprene rubber preferably contains 3 to 7% by weight of carboxylic acid or an alkali metal salt of a carboxylic acid. By containing 3% by weight or more, excellent emulsion stability is achieved during chloroprene polymerization, and by containing 7% by weight or less, a rubber product having excellent processability and stable quality is obtained.

[0020] In the emulsion polymerization of chloroprene rubber, for example, the above-mentioned monomers are mixed with an emulsifier, water, a polymerization initiator, a chain transfer agent, other stabilizers, etc., and polymerization is carried out at a predetermined temperature, and a polymerization terminator is added at a predetermined polymerization conversion rate to terminate the polymerization.

[0021] Examples of the emulsifier include alkali metal salts of carboxylic acids and alkali metal salts of sulfonic acids, such as alkali metal salts of rosin acid, alkali metal salts of alkylbenzenesulfonic acids, alkali metal salts of fatty acids, alkali metal salts of alkenylsuccinic acids, alkali metal salts of polycarboxylic acids, nonionic emulsifiers such as polyoxyethylene alkyl ethers, and water-soluble polymer compounds. Examples of the alkali metal salts include lithium, sodium, potassium, and cesium. These may be used alone or in combination of two or more, but from the viewpoints of polymerization stability, cohesiveness during drying, and rubber performance, it is preferable to use an alkali metal salt of carboxylic acid, and it is particularly preferable to use an alkali metal salt of rosin acid, and more preferably a potassium salt of rosin acid.

[0022] The amount of the emulsifier is not particularly limited, but considering the stability of the chloroprene rubber latex obtained after polymerization, the amount is preferably 3 to 10 parts by weight per 100 parts by weight of the chloroprene rubber, and the amount of the alkali metal salt of the carboxylic acid is preferably 3 to 8 parts by weight, more preferably 5 to 7 parts by weight.

[0023] In order to maintain the stability of the polymerization solution, it is preferable to adjust the pH to 11 or more by using a pH adjuster. At a pH of 11 or more, the alkali metal salt of the carboxylic acid is not acidified, and the stability of the latex is not reduced. Examples of the pH adjuster include basic compounds such as sodium hydroxide, potassium hydroxide, sodium phosphate, potassium phosphate, triethylamine, diethylamine, triethanolamine, diethanolamine, ethanolamine, and ammonia, and any one or more of them can be used alone or in combination.

[0024] As the initiator for emulsion polymerization, known free radical substances can be used, for example, peroxides such as potassium persulfate and ammonium persulfate, hydrogen peroxide, inorganic or organic peroxides such as tertiary butyl hydroperoxide, etc. These can be used alone or in combination with reducing substances such as thiosulfates, thiosulfites, hydrosulfites, organic amines, etc. in a redox system.

[0025] Examples of the chain transfer agent include molecular weight regulators such as alkyl mercaptan, halogenated hydrocarbon, alkyl xanthogen disulfide, alkyl xanthogen polysulfide, and sulfur, and n-dodecyl mercaptan is preferred for mercaptan modification from the viewpoint of workability. The amount of the chain transfer agent is not particularly limited as long as it is an amount used in general radical polymerization for molecular weight adjustment, but it is preferably 0.01 to 1.0% by weight relative to 100% by weight of the monomer mixture other than the chain transfer agent in order to achieve the molecular weight and toluene insoluble content of the resulting polymer as desired, and further, to obtain the flexibility and good mechanical properties of the vulcanized rubber obtained by dip molding.

[0026] The polymerization temperature is not particularly limited, but is preferably in the range of 10 to 50°C.

[0027] The time when the polymerization is to be completed is not particularly limited, but a monomer conversion rate of 60% or more can ensure the production volume, and a monomer conversion rate of 95% or less prevents the polymerization time from becoming too long, so that a range of 60 to 95% is preferable in terms of productivity.

[0028] The polymerization terminator is not particularly limited as long as it is a commonly used terminator, and examples thereof include phenothiazine, 2,6-t-butyl-4-methylphenol, and hydroxylamine.

[0029] In the case of sulfur-modified chloroprene copolymerized with sulfur, it is possible to add a deflocculating agent and a deflocculating assistant to the polymerization-stopped latex and continue deflocculation until a suitable Mooney viscosity is obtained. The deflocculating agent includes thiuram compounds such as tetraethylthiuram disulfide, tetrabutylthiuram disulfide, and tetraoctylthiuram disulfide, which can be added in an emulsified state using the above-mentioned emulsifiers. The deflocculating reaction initiator includes thiocarbamic acid compounds such as sodium dibutyldithiocarbamate and ammonium dimethyldithiocarbamate.

[0030] As the chloroprene rubber, mercaptan-modified, xanthogen-modified or sulfur-modified chloroprene rubber is used.

[0031] Cellulose nanofibers are cellulose fibers contained in wood that have been defibrated to an average fiber diameter of several nanometers to several tens of nanometers.

[0032] Cellulose defibration processes include those that are primarily mechanical, and those that use chemical processing to impart various functional groups and then use mechanical processing in combination to defibrate the cellulose down to the single nano level.

[0033] Cellulose nanofibers modified by chemical treatment are much more expensive than unmodified ones, so unmodified ones are preferable. Furthermore, when the hydroxymethyl groups of cellulose are modified by chemical treatment with carboxylic acid and carboxylate, the dispersion state of the cellulose nanofiber in the rubber deteriorates, so it is preferable that the cellulose nanofiber does not have carboxylic acid and carboxylate.

[0034] Furthermore, it is preferable to use cellulose nanofibers whose surface tension of a 1% by weight aqueous dispersion of cellulose nanofibers is 60 mN / m or less. Examples of such cellulose nanofibers include cellulose nanofibers having amphiphilicity. Amphiphilicity means that cellulose nanofibers have both a hydrophilic part with high affinity to water and a hydrophobic part with low affinity to water, and can be obtained by colliding a water-suspended sample at high speed as described in Japanese Patent No. 5419120. By having amphiphilicity, the affinity between cellulose and hydrophobic rubber is high, and a large improvement effect on mechanical properties can be obtained with a smaller amount of mixture. Generally, the surface tension of pure water is about 72 mN / m, but the greater the hydrophobicity, the smaller the surface tension. If the surface tension of an aqueous dispersion of cellulose nanofibers is 60 mN / m or less at a concentration of 1% by weight, it has amphiphilicity and high affinity with rubber.

[0035] Furthermore, wood and other materials used as raw materials for cellulose nanofibers contain lignin, but since cellulose nanofibers containing a large amount of lignin may impair the stability of chloroprene latex, the amount of lignin contained is preferably 20% by weight or less, more preferably 10% by weight or less, and even more preferably 5% by weight or less.

[0036] In the present invention, it is preferable to use cellulose nanofibers that are defibrated only by mechanical treatment without chemical treatment, so that the cellulose nanofibers are not expensive and the dispersion state of the cellulose nanofibers in the rubber is not deteriorated. Also, it is preferable that the cellulose nanofibers have amphiphilicity in order to increase the affinity with the rubber.

[0037] It is desirable to use cellulose nanofibers having an average fiber diameter of 10 to 300 nm, preferably 10 to 100 nm, and an average fiber length of 0.3 to 200 μm, preferably 0.3 to 100 μm.

[0038] In the rubber composition of the present invention, the content of the cellulose nanofiber is 0.1 to 3.5 parts by weight, preferably 0.4 to 3.0 parts by weight, based on 100 parts by weight of the chloroprene rubber. If the content is less than 0.1 part by weight, the effect of improving the die swelling ratio cannot be obtained, and if it exceeds 3.5 parts by weight, the handling property during mixing of the cellulose nanofiber deteriorates.

[0039] The rubber composition of the present invention contains, as a reinforcing agent or filler, at least one selected from the group consisting of carbon black, silica, clay, calcium carbonate, talc, titanium oxide, barium sulfate, aluminum hydroxide, wollastonite and diatomaceous earth in a total amount of 10 to 200 parts by weight, preferably 30 to 150 parts by weight, based on 100 parts by weight of chloroprene rubber. If the content is less than 10 parts by weight, the die swelling of the molded product after extrusion processing is significantly deteriorated and the shape retention is deteriorated. On the other hand, if the content exceeds 200 parts by weight, physical properties such as tensile properties, elongation, and compression set after vulcanization are deteriorated.

[0040] The rubber composition can be obtained by mixing an aqueous dispersion of cellulose nanofibers with chloroprene latex to prepare a cellulose nanofiber-dispersed rubber latex mixture, removing water from the cellulose nanofiber-dispersed rubber latex mixture, and mixing the mixture with a reinforcing agent, a filler, an acid acceptor, a vulcanizing agent, and other chemicals such as a plasticizer, a processing aid, and an antioxidant, as necessary.

[0041] The chloroprene latex is not particularly limited as long as it is chloroprene rubber emulsified and dispersed in water with an emulsifier, and examples of the chloroprene latex include an emulsion obtained by emulsion polymerization of an unsaturated monomer copolymerizable with a chloroprene monomer, and an emulsion obtained by dissolving chloroprene rubber in an organic solvent such as toluene and then mixing it with water and an emulsifier.

[0042] There are no particular limitations on the method for mixing the chloroprene rubber latex and the aqueous dispersion of cellulose nanofibers, and the mixture can be obtained by using a propeller-type stirring device, a homomixer, a high-pressure homogenizer, or the like, and mixing the chloroprene latex and the aqueous dispersion of cellulose nanofibers until they appear uniform (no lumps, etc.).

[0043] Methods for removing water (drying methods) from the cellulose nanofiber-dispersed rubber latex mixture include heat drying, coagulation with acid or salt, and freeze drying, but coagulation leaves emulsifier, coagulation liquid, and water inside the rubber, so the most efficient and easiest method for drying is to precipitate the rubber by freezing (freeze coagulation), wash off the excess emulsifier, etc., and then dry with hot air, which is preferred. Furthermore, it is even more preferred to freeze-dry the cellulose nanofiber-dispersed rubber latex mixture at a pH of 10 or less so that the rubber can be easily precipitated.

[0044] In the method of freezing and coagulating the cellulose nanofiber-dispersed rubber latex mixture and drying it, the viscosity of the cellulose nanofiber-dispersed rubber latex mixture is preferably 1000 mPa s or less, and more preferably 600 mPa or less. If the viscosity exceeds 1000 mPa s, compatibility with current manufacturing equipment will be significantly reduced, making it difficult to obtain a rubber composition.

[0045] Furthermore, by making the solids content of the cellulose nanofiber-dispersed rubber latex mixture 20% by weight or more, the strength of the rubber is increased and handling during continuous production is improved; from the standpoint of balance with viscosity, a solids content of 20% by weight or more and 40% by weight or less, and even more preferably 25% by weight or more and 35% by weight or less, is preferred.

[0046] The obtained cellulose nanofiber-containing rubber composition can be mixed with reinforcing agents, fillers, acid acceptors, vulcanizing agents, and other chemicals such as plasticizers, processing aids, and antioxidants as necessary. Vulcanized rubber can be obtained by vulcanizing the rubber composition at an appropriate vulcanization temperature until it cures to about 90% against the maximum torque of the test material.

[0047] The rubber composition obtained exhibits superior die swelling ratio and scorch resistance compared to rubber compositions not containing cellulose nanofibers, and can be used in various extrusion molding applications. In addition, the vulcanized rubber obtained by vulcanization after extrusion molding exhibits excellent dimensional stability.

[0048] The rubber composition has a die swell ratio of 1.4 or less at a temperature of 70° C. and a shear rate of 100 (1 / sec), Die swell ratio at a temperature of 70°C and a shear rate of 300 (1 / sec) is 1.5 or less. Die swell ratio at a temperature of 70°C and a shear rate of 500 (1 / sec) is 1.55 or less. Die swell ratio at a temperature of 70°C and a shear rate of 1000 (1 / sec) is 1.75 or less and has an excellent die swell ratio.

[0049] Moreover, the rubber composition has an excellent scorch resistance, with a t5 of 12 minutes or more and a t35 of 18 minutes or more in a Mooney scorch test. EXAMPLES

[0050] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples.

[0051] <Preparation of chloroprene latex> 0.2 parts by weight of mercaptan was added to 100 parts by weight of chloroprene as a monomer mixture, and mixed and stirred with an emulsifying aqueous solution containing 4.0 parts by weight of potassium salt of rosin acid, 0.3 parts by weight of sodium salt of condensation product of naphthalenesulfonic acid and formaldehyde, 0.3 parts by weight of sulfate salt of oleic acid, 0.2 parts by weight of sodium hydroxide, and 100 parts by weight of water to emulsify, and polymerization was carried out by adding a polymerization catalyst consisting of 0.1 parts by weight of potassium persulfate, 0.01 parts by weight of sodium anthraquinone-β-sulfonate, and 20 parts by weight of water at a constant speed by a pump. The polymerization was carried out by adding the polymerization catalyst until the polymerization conversion rate reached 70%, and the polymerization was stopped by adding a polymerization terminator consisting of 0.01 parts by weight of phenothiazine, 5.0 parts by weight of chloroprene, and 0.5 parts by weight of water. Subsequently, unreacted chloroprene was removed and recovered by steam stripping under reduced pressure to obtain a mercaptan-modified chloroprene rubber latex.

[0052] Also, 0.5 parts by weight of xanthogen was added to 100 parts by weight of chloroprene, and mixed and stirred with an emulsifying aqueous solution containing 4.0 parts by weight of potassium salt of rosin acid, 0.3 parts by weight of sodium salt of condensation product of naphthalenesulfonic acid and formaldehyde, 0.3 parts by weight of sodium salt of condensation product of naphthalenesulfonic acid and formaldehyde, 0.2 parts by weight of sodium hydroxide, and 100 parts by weight of water to emulsify, and a polymerization catalyst consisting of 0.1 parts by weight of potassium persulfate, 0.01 parts by weight of sodium anthraquinone-β-sulfonate, and 20 parts by weight of water was added at a constant speed by a pump to polymerize. The polymerization was carried out by adding the polymerization catalyst until the polymerization conversion rate reached 70%, and the polymerization was stopped by adding a polymerization terminator consisting of 0.01 parts by weight of phenothiazine, 5.0 parts by weight of chloroprene, and 0.5 parts by weight of water. Subsequently, unreacted chloroprene was removed and recovered by steam stripping under reduced pressure to obtain a latex of xanthogen-modified chloroprene polymer A. Next, a latex of mercaptan-modified chloroprene polymer B was obtained in the same manner as the chloroprene polymer A, except that the polymerization recipe was changed to 0.2 parts by weight of mercaptan per 100 parts by weight of chloroprene, and the polymerization addition rate was set to 90%. The latexes of chloroprene polymers A and B were mixed in a ratio of 4:1 to obtain an extrusion grade chloroprene latex.

[0053] <Measurement of the average fiber diameter of cellulose nanofibers> The cellulose nanofibers were diluted with pure water to a concentration of 0.1 wt%, and then filtered and dried. After this, an osmium coating was applied, and SEM observation was performed at a magnification of 20,000 times using a JEOL Ltd. FE-SEM JSM-7100F. From the obtained observation image, 100 fibers were randomly selected, and the fiber diameter was measured, and the average value was taken as the average fiber diameter.

[0054] <Preparation of chloroprene rubber containing cellulose nanofibers> A specified amount of an aqueous dispersion of cellulose nanofiber (Nanoforest, manufactured by Chuetsu Pulp Industries Co., Ltd.) was added to the chloroprene rubber latex and mixed at 2,000 rpm for 10 minutes using an auto homogenizer (PRIMIX, manufactured by Primix Corporation), after which the polymer was precipitated by freeze coagulation and dried.

[0055] <Mooney Scorch Measurement> Using a Mooney Viscometer (Shimadzu Corporation: Automatic Mooney Viscometer SMV-301), test pieces were collected and measured in accordance with JIS K 6300-1:2013 to obtain Vm, which is the minimum Mooney viscosity, t5, which is the time it takes for the viscosity to rise by 5M from Vm, and t35, which is the time it takes for the viscosity to rise by 35M.

[0056] <Die swell ratio measurement> The temperature inside the cylinder of a capillary rheometer (ARC2020 manufactured by Alpha Technologies) was set to 70°C, and an orifice length of 1.524 mm, φ1.524 mm, and L / D = 1 were used. The rubber composition was charged, and after a temperature control period of 2 minutes had elapsed, the diameter of the extrudate obtained by extruding at a specified shear rate was divided by the diameter of the orifice to obtain the die swell ratio.

[0057] <Preparation of vulcanized product> The resulting rubber composition was press-vulcanized at 160° C. for 20 minutes to prepare a vulcanized sheet.

[0058] <Hardness measurement of vulcanized material> The hardness of the obtained vulcanized sheet was evaluated according to JIS K6253 (2012). Type A was selected as the durometer.

[0059] <Measurements of tensile strength, elongation and 100% tensile stress of rubber vulcanizates> Test specimens were punched out from the obtained vulcanized sheet, and the tensile strength, elongation, and 100% tensile stress (M100) were evaluated according to JIS K6251 (2017). For the dumbbell-shaped test specimens, No. 3 type was selected, and evaluation was performed under conditions of a tensile speed of 500 mm / min and 23°C.

[0060] Example 1 A water dispersion of cellulose nanofibers produced by mechanical defibration means (Nanoforest, manufactured by Chuetsu Pulp Co., Ltd., solid content concentration: 3% by weight, average fiber width: approximately 50 nm, average fiber length: approximately 100 μm, lignin content 1% by weight or less, unmodified, amphiphilic) was mixed with 100 parts by weight of mercaptan-modified chloroprene rubber and stirred for 10 minutes using the method described above to obtain a cellulose nanofiber-dispersed rubber latex mixture. The amount of cellulose nanofiber mixed was set to an amount that would result in a cellulose content of 0.4 parts by weight per 100 parts by weight of the solid rubber component.

[0061] For 100 parts by weight of chloroprene rubber containing this cellulose nanofiber, 4 parts by weight of magnesium oxide (Kyowa Chemical Industry Co., Ltd.: Kyowamag #150), 0.5 parts by weight of stearic acid (Shin-Nihon Rika Co., Ltd.: Stearic Acid 300), 2 parts by weight of selected special wax (Ouchi Shinko Chemical Co., Ltd.: Sunnock), 3 parts by weight of polyethylene wax (Honeywell Co., Ltd.: AC 617A), 2 parts by weight of antioxidant octylated diphenylamine (ODPA) (Ouchi Shinko Chemical Co., Ltd.: Nocrac AD-F), HAF carbon black (Tokai Carbon Co., Ltd.: Seast 3) in the weight parts shown in Table 1, 40 parts by weight of clay (Shiraishi Calcium Co., Ltd.: CROWN CLAY), 20 parts by weight of calcium carbonate (Shiraishi Kogyo Co., Ltd.: Hakuenka CC), naphthenic oil (Japan Sun Oil Co., Ltd.: SUNTHENE After cooling, 5 parts by weight of zinc oxide (manufactured by Sakai Chemical Industry Co., Ltd.: zinc oxide type 2), 1.0 part by weight of accelerator 2-imidazoline-2-thiol (ETU) (manufactured by Sanshin Chemical Industry Co., Ltd.: Suncerer #22-C), and 0.4 part by weight of accelerator dibenzothiazole disulfide (MBTS) (manufactured by Ouchi Shinko Chemical Industry Co., Ltd.: Noccela DM) were mixed in an open roll mixer to obtain a rubber composition.

[0062] From the obtained rubber composition, a rubber composition compound and a vulcanized sheet were obtained according to the above-mentioned method, and measurements were carried out for Mooney scorch, die swell ratio, hardness, tensile strength, elongation, and 100% tensile stress (M100). The results are shown in Table 1. As shown in Table 1, the die swell ratio was improved in the shear rate range of 100 to 1000 (1 / sec) compared to Comparative Example 1, which does not contain cellulose nanofibers, which will be described later. Furthermore, the Mooney scorch test also showed improvements at t5 and t35 compared to Comparative Example 1, with all results being good.

[0063] Example 2 A rubber composition compound and a vulcanized sheet were obtained in the same manner as in Example 1, except that the content of cellulose nanofiber was set to 1.0 part by weight, and the amount of HAF carbon black was adjusted so as to obtain a hardness similar to that of Example 1, and measurements of hardness, tensile strength, elongation, and 100% tensile stress (M100) were carried out. The results are shown in Table 1. As shown in Table 1, the die swell ratio was improved in the shear rate range of 100 to 1000 (1 / sec) compared to Comparative Example 1 and Example 1, which do not contain cellulose nanofiber, which will be described later. Furthermore, the Mooney scorch test values ​​t5 and t35 were also improved compared to Comparative Example 1 and Example 1, and all of the results were good.

[0064] Example 3 A rubber composition compound and a vulcanized sheet were obtained in the same manner as in Example 1, except that the content of cellulose nanofiber was set to 2.0 parts by weight, and the amount of HAF carbon black was adjusted so as to obtain a hardness similar to that of Example 1, and measurements of hardness, tensile strength, elongation, and 100% tensile stress (M100) were carried out. The results are shown in Table 1. As shown in Table 1, the die swell ratio was improved in the shear rate range of 100 to 1000 (1 / sec) compared to Comparative Example 1, Example 1, and Example 2, which do not contain cellulose nanofiber, which will be described later. Furthermore, the t5 and t35 values ​​in the Mooney scorch test were also improved compared to Comparative Example 1, Example 1, and Example 2, and all of them were good results.

[0065] Example 4 A rubber composition compound and a vulcanized sheet were obtained in the same manner as in Example 1, except that the content of cellulose nanofiber was set to 3.0 parts by weight, and the amount of HAF carbon black was adjusted so as to obtain a hardness similar to that of Example 1, and measurements of hardness, tensile strength, elongation, and 100% tensile stress (M100) were carried out. The results are shown in Table 1. As shown in Table 1, the die swell ratio was improved in the shear rate range of 100 to 1000 (1 / sec) compared to Comparative Example 1 and Examples 1 to 3, which do not contain cellulose nanofiber, which will be described later. Furthermore, the Mooney scorch test values ​​t5 and t35 were also improved compared to Comparative Example 1 and Examples 1 to 3, and all of them showed good results.

[0066] Example 5 The content of cellulose nanofiber was set to 1.0 part by weight, the amount of HAF carbon black was adjusted so as to obtain the same hardness as in Example 1, and 40 parts by weight of talc (ImerFlex T20 manufactured by Imerys Specialties Japan Co., Ltd.) was used instead of clay (CROWN CLAY manufactured by Shiraishi Calcium Co., Ltd.) was used. A rubber composition compound and a vulcanized sheet were obtained in the same manner as in Example 1, and measurements of hardness, tensile strength, elongation, and 100% tensile stress (M100) were carried out. The results are shown in Table 1. From Table 1, the die swell ratio was improved in the shear rate range of 100 to 1000 (1 / sec) compared to Comparative Example 3 not containing cellulose nanofiber, which will be described later. In addition, in the Mooney scorch test, t5 and t35 of Comparative Example 3 were further improved, with t5 being 12 minutes or more and t35 being 18 minutes or more, and both were good results.

[0067] Example 6 The content of cellulose nanofiber was set to 1.0 part by weight, the amount of HAF carbon black was adjusted so as to obtain the same hardness as in Example 1, and the clay (CROWN CLAY manufactured by Shiraishi Calcium Co., Ltd.) was replaced with 33 parts by weight of silica (Nipsil VN3 manufactured by Tosoh Silica Co., Ltd.), and naphthenic oil (SUNTHENE 415 manufactured by Nippon Sun Oil Co., Ltd.) was changed from 15 parts by weight to 25 parts by weight. A rubber composition compound and a vulcanized sheet were obtained in the same manner as in Example 1, and measurements of hardness, tensile strength, elongation, and 100% tensile stress (M100) were carried out. The results are shown in Table 1. From Table 1, the die swell ratio was improved in the shear rate range of 100 to 1000 (1 / sec) compared to Comparative Example 4 which does not contain cellulose nanofiber, which will be described later. In addition, in the Mooney scorch test, t5 and t35 of Comparative Example 4 were improved further, with t5 being 12 minutes or more and t35 being 18 minutes or more, and both were good results.

[0068] Example 7 The content of cellulose nanofiber was set to 1.0 part by weight, the amount of HAF carbon black was adjusted so as to obtain the same hardness as in Example 1, 20 parts by weight of talc (ImerFlex T20 manufactured by Imerys Specialties Japan Co., Ltd.) was used instead of clay (CROWN CLAY manufactured by Shiraishi Calcium Co., Ltd.), 30 parts by weight of titanium oxide (R-820 manufactured by Ishihara Sangyo Kaisha, Ltd.), and 0.5 parts by weight of tetramethylthiuram disulfide (TMTD) (Noccela TT-P manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) were used as the vulcanization accelerator. Except for this, a rubber composition compound and a vulcanized sheet were obtained in the same manner as in Example 1, and measurements of hardness, tensile strength, elongation, and 100% tensile stress (M100) were carried out. The results are shown in Table 1. From Table 1, the die swell ratio was improved in the range of shear rates of 100 to 1000 (1 / sec) compared to Comparative Example 5 not containing cellulose nanofiber, which will be described later. In addition, in the Mooney scorch test, t5 and t35 of Comparative Example 5 were improved, with t5 being 12 minutes or more and t35 being 18 minutes or more, and both results being good.

[0069] Example 8 The content of cellulose nanofiber was set to 1.0 part by weight, the amount of HAF carbon black was adjusted so as to obtain the same hardness as in Example 1, and 20 parts by weight of talc (ImerFlex T20 manufactured by Imerys Specialties Japan Co., Ltd.) and 30 parts by weight of barium sulfate (precipitated barium sulfate 100 manufactured by Sakai Chemical Industry Co., Ltd.) were used instead of clay (CROWN CLAY manufactured by Shiraishi Calcium Co., Ltd.). A rubber composition compound and a vulcanized sheet were obtained in the same manner as in Example 1, and measurements of hardness, tensile strength, elongation, and 100% tensile stress (M100) were carried out. The results are shown in Table 1. From Table 1, the die swell ratio was improved in the shear rate range of 100 to 1000 (1 / sec) compared to Comparative Example 6, which does not contain cellulose nanofiber, which will be described later. In addition, in the Mooney scorch test, t5 and t35 of Comparative Example 5 were improved further, with t5 being 12 minutes or more and t35 being 18 minutes or more, and both were good results.

[0070] Example 9 The content of cellulose nanofiber was 1.0 part by weight, and clay (Shiraishi Calcium Co., Ltd.: CROWN The rubber composition compound and vulcanized sheet were obtained in the same manner as in Example 1, except that 0 parts by weight of calcium carbonate (Shiraishi Kogyo Co., Ltd.: Hakuenka CC), 0 parts by weight of calcium carbonate (Shiraishi Kogyo Co., Ltd.: Hakuenka CC), and 55 parts by weight of HAF carbon black were used to adjust the hardness to the same level as in Example 1, and 1.0 parts by weight of 2-imidazoline-2-thiol (ETU) (Sanshin Chemical Co., Ltd.: Suncerer #22-C), 1.2 parts by weight of trimethylthiourea (Ouchi Shinko Chemical Co., Ltd.: Noccela TMU), and 2.0 parts by weight of tetramethylthiuram disulfide (TMTD) (Ouchi Shinko Chemical Co., Ltd.: Noccela TT-P) were used instead of 0.4 parts by weight of dibenzothiazole disulfide (MBTS) (Ouchi Shinko Chemical Co., Ltd.: Noccela DM) as the vulcanization accelerator. The hardness, tensile strength, elongation, and 100% tensile stress (M100) were measured. The results are shown in Table 1. From Table 1, it can be seen that the die swell ratio of Comparative Example 7, which does not contain cellulose nanofibers described later, was improved further, with a die swell ratio of 1.4 or less at a temperature of 70°C and a shear rate of 100 (1 / sec), a die swell ratio of 1.5 or less at a temperature of 70°C and a shear rate of 300 (1 / sec), a die swell ratio of 1.55 or less at a temperature of 70°C and a shear rate of 500 (1 / sec), and a die swell ratio of 1.75 or less at a temperature of 70°C and a shear rate of 1000 (1 / sec). Furthermore, the Mooney scorch test also showed improvements in t5 and t35 compared to Comparative Example 7, with all of the results being good.

[0071] Comparative Example 1 A rubber composition compound and a vulcanized sheet were obtained in the same manner as in Example 1, except that cellulose nanofibers were not mixed and the amount of HAF carbon black was adjusted so that the hardness was similar to that of Example 1, and measurements of hardness, tensile strength, elongation, and 100% tensile stress (M100) were carried out. The results are shown in Table 1. As shown in Table 1, the die swell ratio was inferior to Examples 1 to 4, which contained cellulose nanofibers, in the shear rate range of 100 to 1000 (1 / sec), and the results of the Mooney scorch test at t5 and t35 were also inferior to Examples 1 to 4.

[0072] Comparative Example 2 A rubber composition compound and a vulcanized sheet were obtained in the same manner as in Comparative Example 1, except that 100 parts by weight of extrusion grade chloroprene rubber was used, and measurements of hardness, tensile strength, elongation, and 100% tensile stress (M100) were carried out. The results are shown in Table 1. From Table 1, the die swell ratio was inferior to Example 3 but better than Example 2 in the shear rate range of 100 to 300 (1 / sec). Also, at a shear rate of 500 (1 / sec), it was inferior to Example 4 but better than Example 3. Furthermore, at a shear rate of 1000 (1 / sec), it was better than Example 4. However, the results of the Mooney scorch test at t5 and t35 were inferior to those of Examples 1 to 4.

[0073] Comparative Example 3 A rubber composition compound and a vulcanized sheet were obtained in the same manner as in Example 1, except that cellulose nanofibers were not mixed, the amount of HAF carbon black was adjusted so that the hardness was similar to that of Example 1, and the filler was changed in the same manner as in Example 5. The hardness, tensile strength, elongation, and 100% tensile stress (M100) were measured. The results are shown in Table 1. As shown in Table 1, the die swell ratio was inferior to that of Example 5 containing cellulose nanofibers in the shear rate range of 100 to 1000 (1 / sec). In particular, the die swell ratio exceeded 1.55 at a shear rate of 500 (1 / sec). In addition, the results of the Mooney scorch test at t5 and t35 were also inferior to those of Example 5.

[0074] Comparative Example 4 A rubber composition compound and a vulcanized sheet were obtained in the same manner as in Example 1, except that cellulose nanofibers were not mixed, the amount of HAF carbon black was adjusted so that the hardness was similar to that of Example 1, and the filler was changed in the same manner as in Example 6. Hardness, tensile strength, elongation, and 100% tensile stress (M100) were measured. The results are shown in Table 1. As shown in Table 1, the die swell ratio was inferior to Example 6, which contained cellulose nanofibers, in the shear rate range of 100 to 1000 (1 / sec), and the results of the Mooney scorch test at t5 and t35 were also inferior to Example 6.

[0075] Comparative Example 5 A rubber composition compound and a vulcanized sheet were obtained in the same manner as in Example 1, except that cellulose nanofibers were not mixed, the amount of HAF carbon black was adjusted so that the hardness was similar to that of Example 1, and the filler and vulcanization accelerator were changed as in Example 7. Hardness, tensile strength, elongation, and 100% tensile stress (M100) were measured. The results are shown in Table 1. As shown in Table 1, the die swell ratio was inferior to Example 7, which contained cellulose nanofibers, in the shear rate range of 100 to 1000 (1 / sec), and the results of the Mooney scorch test at t5 and t35 were also inferior to Example 7.

[0076] Comparative Example 6 A rubber composition compound and a vulcanized sheet were obtained in the same manner as in Example 1, except that cellulose nanofibers were not mixed, the amount of HAF carbon black was adjusted so that the hardness was similar to that of Example 1, and the filler was changed in the same manner as in Example 8. Hardness, tensile strength, elongation, and 100% tensile stress (M100) were measured. The results are shown in Table 1. As shown in Table 1, the die swell ratio was inferior to Example 8, which contained cellulose nanofibers, in the shear rate range of 100 to 1000 (1 / sec), and the results of the Mooney scorch test at t5 and t35 were also inferior to Example 8.

[0077] Comparative Example 7 A rubber composition compound and a vulcanized sheet were obtained in the same manner as in Example 1, except that cellulose nanofibers were not mixed, the amount of HAF carbon black was adjusted so that the hardness was similar to that of Example 1, and the filler and vulcanization accelerator were changed as in Example 9. Hardness, tensile strength, elongation, and 100% tensile stress (M100) were measured. The results are shown in Table 1. As shown in Table 1, the die swell ratio was inferior to Example 9, which contained cellulose nanofibers, in the shear rate range of 100 to 1000 (1 / sec), and the results of the Mooney scorch test at t5 and t35 were also inferior to Example 9.

[0078] Comparative Example 8 A rubber composition compound and a vulcanized sheet were obtained in the same manner as in Example 1, except that the content of cellulose nanofiber was 1.0 part by weight, only 8 parts by weight of HAF carbon black was added as component (C), and no plasticizer was added, and measurements of hardness, tensile strength, elongation, and 100% tensile stress (M100) were carried out. The results are shown in Table 1. Table 1 shows that the die swell ratio showed a very large value in the shear rate range of 100 to 1000 (1 / sec).

[0079] [Table 1]

Claims

1. Contains the following components (A) to (C): A die swell ratio at a temperature of 70° C. and a shear rate of 100 (1 / sec) is 1.4 or less. A die swell ratio at a temperature of 70° C. and a shear rate of 300 (1 / sec) is 1.5 or less. A die swell ratio at a temperature of 70° C. and a shear rate of 500 (1 / sec) is 1.55 or less. A chloroprene rubber composition having a die swell ratio of 1.75 or less at a temperature of 70°C and a shear rate of 1000 (1 / sec), and having a t5 of 12 minutes or more and a t35 of 18 minutes or more in a Mooney scorch test. Component (A): mercaptan-modified, xanthogen-modified or sulfur-modified chloroprene rubber. Component (B): 0.1 to 3.5 parts by weight of cellulose nanofibers having an average fiber diameter of 10 to 300 nm, an average fiber length of 0.3 to 200 μm, a lignin content of 20% by weight or less, and a hydroxymethyl group not modified with a carboxylic acid or a carboxylate, per 100 parts by weight of chloroprene rubber. Component (C): 10 to 200 parts by weight in total of at least one selected from the group consisting of carbon black, silica, clay, calcium carbonate, talc, titanium oxide, barium sulfate, aluminum hydroxide, wollastonite, and diatomaceous earth, per 100 parts by weight of chloroprene rubber.

2. The rubber composition according to claim 1 , wherein the cellulose nanofibers are unmodified and defibrated only by mechanical treatment.

3. The rubber composition according to claim 1, wherein the chloroprene rubber contains 3 to 7% by weight of a carboxylic acid or an alkali metal salt of a carboxylic acid.

4. A vulcanized rubber which is a vulcanizate of the rubber composition according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • JP1975159536A

  • Rubber composition for tire cord coating

    JP1995330961A